The Relationship of General and ADHD Specific Predictors of Substance Use and College Adjustment and Functioning among ADHD College Students - Mochrie, Kirk Dillon (East Carolina University, 2019)
Background: Recent research has demonstrated that ADHD college students are at a higher risk for substance use, academic problems, and psychosocial difficulties compared to non-ADHD students. Less is known about the role of ADHD specific factors on substance use and psychosocial/academic adjustment as well as the possible interaction of substance use and ADHD factors on college adjustment. Purpose: The current research sought to understand predictors of substance use and possible relations between ADHD factors, substance use, and psychosocial/academic adjustment among ADHD college students. Methods: Sixty-six ADHD undergraduates were asked to complete a series of online self-report inventories related to ADHD, substance use, and college adjustment. Participants also completed a semi-structured interview for current ADHD diagnosis, an objective behavioral assessment of ADHD impairment, and answered qualitative questions about ADHD college student functioning. Results: General factors (i.e., substance use history, history of conduct problems, positive expectancies, and peer influence) were good predictors of current substance use and consequences. ADHD specific factors (i.e., severity of ADHD symptoms, impulsivity, emotion dysregulation, and executive functioning deficits) were not predictive of substance use, although several ADHD specific factors significantly predicted substance use consequences. Participants with higher emotion dysregulation as well as executive functioning deficits struggled with more psychosocial/academic difficulties. Higher severity of ADHD symptoms predicted more current symptoms of depression/anxiety and more academic adjustment difficulties. Of note, substance use was not a good predictor of psychosocial/academic outcomes in this sample. However, interactions of alcohol and particularly marijuana with various ADHD specific factors significantly predicted GPA. Discussion: ADHD College students with higher scores on general substance use predictors were more likely to engage in more frequent and heavy substance use with increased negative consequences. Although the ADHD factors did not predict substance use, ADHD students with greater symptoms, higher impulsivity, higher emotion dysregulation, and higher executive functioning deficits were more likely to experience substance-related problems. Overall, severity of ADHD specific factors most increased an individual’s risk for college adjustment difficulties. Targeted prevention and intervention strategies for incoming students with ADHD should be aimed at increasing awareness and coping skills for ADHD as well as incorporate psychoeducation about substance abuse risk.
Keywords: Academic Adjustment; Psychosocial Adjustment; College students--Mental health; Attention-deficit-disordered youth--Education (Higher); College students--Drug use--Prevention; College students--Alcohol use--Prevention